HUBUNGAN USIA IBU PRIMIGRAVIDA DENGAN KEJADIAN DEPRESI ANTEPARTUM - Diah Ayu Fatmawati; Mukhoirotin Mukhoirotin (Universitas Pesantren Tinggi Darul Ulum, 2017)
ABSTRACTDepression in pregnant women can occur in antepartum (during pregnancy) and postpartum (after delivery). Antepartum and postpartum depression both have an effect of morbidity and mortality for pregnant women and childbirth. Some of the factors that affect antepartum depression include the age of pregnant women, education, economic perception and husband's social support. The purpose of this study was to identify the proportion of depression cases occurring in primigravida and some external variables associated with the incidence of antepartum depression. This study was Observational Analytic design with Cross Sectional approach, Subjects in the study of primigravida in health center working area Peterongan Jombang amounted 80 respondents using consecutive sampling technique that meets the inclusion and exclusion criteria. Data collection using questionnaire of demographic data, Edinburgh Postnatal Depression Scale (EPDS) questionnaire, social support questionnaire and indepth interview and data were analized using Chi-square test and logistic regression with significance level α≤0,05. The results showed that there was a significant relationship between maternal age, education, economic perception and social support with antepartum depression (p <0.05). the most powerful variable of influence is the social support with an OR value of 0.011 (95% CI = 0.001-0.116) with a significant value of 0.000. Social support of the Husband is the dominant factor affecting the incidence of antepartum depression. Husband and family should provide support during pregnancy with attention, material and non-material support. Keywords: antepartum depression, maternal age, social support of the husband.